Criminal Enforcement of Copyright as an Important Safeguard for Economic and Security Interests - Vasiu, Ioana; Vasiu, Lucian (European Journal of Sustainable Development, 2019)
Copyright industries represent an important part of the developed economies. The effective protection of copyright fulfills an important role in the advancement of innovation and economic development. However, in the digital economy, the protection of copyrighted works poses numerous and very difficult challenges. The protected works usually targeted by criminals are computer programs, motion pictures, video games, and musical compositions. The estimated or actual harm to copyright owners can amount to billions of dollars. Moreover, these offenses are sometimes perpetrated in connection with other crimes, such as conspiracy to commit racketeering or money laundering. This paper argues that criminal enforcement of copyright can be an important safeguard of economic and information security interests. The paper discusses essential aspects regarding the criminal protection of copyright in the United States. Based on a theoretically-informed, yet empirically-driven approach, which takes into account a large corpus of data, consisting mostly of cases brought to courts of law, the paper discusses the main aspects of the phenomenon. Finally, the paper proposes a number of measures that would improve the protection copyrighted works. Keywords: Copyright, Economic Development, Cybercrime, Infringement, Security, Loss